Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/9130979
|View full text |Cite
|
Sign up to set email alerts
|

Review of Anti-Inflammatory Herbal Medicines

Abstract: Medicinal plants and their secondary metabolites are progressively used in the treatment of diseases as a complementary medicine. Inflammation is a pathologic condition that includes a wide range of diseases such as rheumatic and immune-mediated conditions, diabetes, cardiovascular accident, and etcetera. We introduce some herbs which their anti-inflammatory effects have been evaluated in clinical and experimental studies. Curcuma longa, Zingiber officinale, Rosmarinus officinalis, Borago officinalis, evening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
154
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 98 publications
0
154
0
4
Order By: Relevance
“…Therefore, there is an ongoing search for natural digestive enzyme inhibitors with fewer side effects for prevention or mitigation the symptom of obesity or diabetes. Previous researches have shown that some types of tea exhibited pronounced inhibitory effects towards the activities of α-amylase, lipase and in ammation [8,9]. At present, many treatments involving the use of medicinal plants have been recommended, since most contain compounds with antidiabetic, anti-in ammatory, anti-pyretic and analgesic effects and with low indices of toxicity [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an ongoing search for natural digestive enzyme inhibitors with fewer side effects for prevention or mitigation the symptom of obesity or diabetes. Previous researches have shown that some types of tea exhibited pronounced inhibitory effects towards the activities of α-amylase, lipase and in ammation [8,9]. At present, many treatments involving the use of medicinal plants have been recommended, since most contain compounds with antidiabetic, anti-in ammatory, anti-pyretic and analgesic effects and with low indices of toxicity [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Various herbal drugs being also used to treat inflammation and oxidative stress related complications [9]. Curcuma longa, Zingiber officinale, Boswellia serrata and Rosmarinus officinalis these medicinal plants showed anti-inflammatory activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidences suggested that herbal medicines could attenuate inflammatory response and pain in the joints [13]. Morin, a natural flavonoid that isolated from the Chinese herbs of the Moraceae family, has been known to possess anti-inflammatory effects [14].…”
Section: Introductionmentioning
confidence: 99%